THE EFFECT OF PROFITABILITY, EXECUTIVE CHARACTER AND COMPANY SIZE ON TAX AVOIDANCE - Dani Sopian; Wulan Laelasari; Intan Pramesti Dewi (ZILLZELL MEDIA PRIMA, 2023)
This study aims to determine the effect of profitability, executive character and company size on tax avoidance in companies in the primary consumer goods sector (consumer noncyclical) listed on the Indonesia Stock Exchange for the period 2018-2022. The population in this study was 70 companies. This study used 40 companies in the primary consumer goods sector (consumer noncyclical) listed on the IDX, the sampling technique used was the proportionate stratified random sampling technique from the period 2018-2022 with a sample number of 200 data. The data used are quantitative data sourced from secondary data, then the data collected are analyzed using descriptive analysis methods and multiple linear regression analysis followed by multicollinearity tests, autocorrelation tests, heteroscedasticity tests, normality tests and correlation analysis. Based on the results of the study shows that simultaneously profitability, executive character and company size have an insignificant effect on tax avoidance. And the test results partially show that profitability has a significant positive effect on tax avoidance, executive character has a positive effect is not significant and company size has a negative effect is not significant on tax avoidance.